2012
DOI: 10.1002/adsc.201200588
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Induced Selective Generation of Radicals from Organoborates by Photoredox Catalysis

Abstract: A new strategy for the generation of carbon‐centered radicals via oxidation of alkyl‐, allyl‐, benzyl‐ and arylborates by visible‐light‐driven single electron transfer (SET) photoredox catalysis has been established. The generated radicals smoothly react with TEMPO and electron‐deficient alkenes to afford CO and CC coupling products, respectively. In this radical initiating system, cyclic organo(triol)borates turn out to be useful radical precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
131
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(145 citation statements)
references
References 64 publications
4
131
0
4
Order By: Relevance
“…[69] In contrast with organoboron-based compounds, this class of precursors offers convenient access to primary radical intermediates due to their significantly lower oxidation potential (E 1/2 ox > +1.2 V vs. SCE for primary alkyltrifluoroborates [70] vs. E 1/2 ox = +0.34 to +0.61 V vs. SCE for primary alkylsilicates) [69] Importantly, the precursors can be readily prepared from inexpensive trimethoxysilane derivatives and catechols and are stable upon storage at room temperature. The authors demonstrated the utility of these substrates in a large number of examples based on Giesetype radical additions to electron-deficient alkenes.…”
Section: C(sp 3 )-Organosilicon Substratesmentioning
confidence: 99%
“…[69] In contrast with organoboron-based compounds, this class of precursors offers convenient access to primary radical intermediates due to their significantly lower oxidation potential (E 1/2 ox > +1.2 V vs. SCE for primary alkyltrifluoroborates [70] vs. E 1/2 ox = +0.34 to +0.61 V vs. SCE for primary alkylsilicates) [69] Importantly, the precursors can be readily prepared from inexpensive trimethoxysilane derivatives and catechols and are stable upon storage at room temperature. The authors demonstrated the utility of these substrates in a large number of examples based on Giesetype radical additions to electron-deficient alkenes.…”
Section: C(sp 3 )-Organosilicon Substratesmentioning
confidence: 99%
“…Nevertheless, encouragement was found in cases where thermodynamically unfavorable SETs occur, particularly within the context of an irreversible oxidation or reduction. 22,24 Thus, only a small portion of the oxidation wave need overlap with the potential of the photocatalyst for the reaction to proceed, driven forward by irreversible C−B bond fragmentation.…”
mentioning
confidence: 99%
“…Although thermodynamically unfavorable, such SET processes have been reported. [25] Stern-Volmer quenching studies revealed that cyclobutylaniline 1a quenches the photoexcited 4a while alkynes 2a and 2h showed little quenching (see SI).…”
mentioning
confidence: 99%